Mitochondrial function after associating liver partition and portal vein ligation for staged hepatectomy in an experimental model - Budai, A.; Horváth, G.; Tretter, L.; Radák, Z.; Koltai, E.; Bori, Z.; Torma, F.; Lukáts, Á.; Röhlich, P.; Szijártó, A.; Fülöp, A. (British journal of surgery, 2019)
Background Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a two‐stage strategy to induce rapid regeneration of the remnant liver. The technique has been associated with high mortality and morbidity rates. This study aimed to evaluate mitochondrial function, biogenesis and morphology during ALPPS‐induced liver regeneration. Methods Male Wistar rats (n = 100) underwent portal vein ligation (PVL) or ALPPS. The animals were killed at 0 h (without operation), and 24, 48, 72 or 168 h after intervention. Regeneration rate and proliferation index were assessed. Mitochondrial oxygen consumption and adenosine 5′‐triphosphate (ATP) production were measured. Mitochondrial biogenesis was evaluated by protein level measurements of peroxisome proliferator‐activated receptor γ co‐activator (PGC) 1‐α, nuclear respiratory factor (NRF) 1 and 2, and mitochondrial transcription factor α. Mitochondrial morphology was evaluated by electron microscopy. Results Regeneration rate and Ki‐67 index were significantly raised in the ALPPS group compared with the PVL group (regeneration rate at 168 h: mean(s.d.) 291·2(21·4) versus 245·1(13·8) per cent, P < 0·001; Ki‐67 index at 24 h: 86·9(4·6) versus 66·2(4·9) per cent, P < 0·001). In the ALPPS group, mitochondrial function was impaired 48 h after the intervention compared with that in the PVL group (induced ATP production); (complex I: 361·9(72·3) versus 629·7(165·8) nmol per min per mg, P = 0·038; complex II: 517·5(48·8) versus 794·8(170·4) nmol per min per mg, P = 0·044). Markers of mitochondrial biogenesis were significantly lower 48 and 72 h after ALPPS compared with PVL (PGC1‐α at 48 h: 0·61‐fold decrease, P = 0·045; NRF1 at 48 h: 0·48‐fold decrease, P = 0·028). Mitochondrial size decreased significantly after ALPPS (0·26(0·05) versus 0·40(0·07) μm2; P = 0·034). Conclusion Impaired mitochondrial function and biogenesis, along with the rapid energy‐demanding cell proliferation, may cause hepatocyte dysfunction after ALPPS. Surgical relevance Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a well known surgical strategy that combines liver partition and portal vein ligation. This method induces immense regeneration in the future liver remnant. The rapid volume increase is of benefit for resectability, but the mortality and morbidity rates of ALPPS are strikingly high. Moreover, lagging functional recovery of the remnant liver has been reported recently. In this translational study, ALPPS caused an overwhelming inflammatory response that interfered with the peroxisome proliferator‐activated receptor γ co‐activator 1‐α‐coordinated, stress‐induced, mitochondrial biogenesis pathway. This resulted in the accumulation of immature and malfunctioning mitochondria in hepatocytes during the early phase of liver regeneration (bioenergetic destabilization). These findings might explain some of the high morbidity if confirmed in patients. Defines the biochemical basis